Impact of pulmonary hypertension on arteriovenous fistula failure of hemodialysis patients: A 10 years follow-up cohort study. Issue 2 (March 2023) - Song, Li; Quan, Zi-Lin; Zhao, Li-Yan; Cui, Dong-Mei; Zhong, Mi; Zhou, Li-Fang; Sun, Chun-Yan; Chen, Ying-Gui; Mo, Ya-Wen; Feng, Zhonglin; Tao, Yiming; Ye, Zhiming; et al.
Background: Pulmonary hypertension (PH) is common in patients with end-stage renal disease (ESRD). Arteriovenous fistulas (AVF) creation may involve in the pathogenesis of PH. The aim of this study was to explore the impact of PH after AVF creation on the AVF failure rate in maintenance hemodialysis (MHD) patients. Methods: From January 1, 2009, to January 1, 2019, we retrospectively collected data of 578 MHD patients in Guangdong Provincial People's Hospital Blood Purification Center, China. Patients were followed-up until AVF failure or death or May 25, 2020. According to the systolic pulmonary artery pressure (SPAP) within 1 year after the establishment of AVF, the MHD patients were divided into three groups: SPAP ⩽ 35 mmHg, 35 < SPAP < 45 mmHg, SPAP ⩾ 45 mmHg. The primary outcome was AVF failure defined as AVF cannot complete hemodialysis. The secondary outcomes were all-cause mortality. Results: A total of 578 patients were analyzed. The average age was 60.66 ± 15.34 years (58.1% men). Of these, 26.1% of patients were reported PH. The SPAP exhibited a left-skewed nonparametric distribution and the overall SPAP after the creation of AVF was 39.00 (29.00–52.00) mmHg. The median follow-up was 5.8 (5.5–6.3) years. Overall, 12.8% (74/578) patients were reported AVF failure events. There was no significant difference in AVF failure rate among three groups ( p = 0.070). A total of 111 (19.2%) died during the follow-up period. Compared with the SPAP ⩽35 mmHg group, only the all-cause death rate significantly increased in MHD patients with PH ( p < 0.001). Conclusions: The secondary pulmonary hypertension after AVF creation did not increase the risk of AVF failure in MHD patients, but significantly increased the risk of mortality for this portion of the patients. Future larger sample sizes, multi-center, and prospective trials are needed to make sure which type of access will benefit on their survival for MHD patients with SPAP ⩾35 mmHg.